Collection Assessment and Development at a U.S. Membership Library: A Case Study. Issue 2 (2nd April 2016) - Kelly, Robert
ABSTRACT: Due to fiscal challenges of a nonprofit subscription (also known as "membership") library in the post-2008 economy, a cost-effective collection assessment and subsequent collections development policy was initiated, leveraging historic acquisition patterns over a 200-year period. The inaugural comprehensive collections policy underlines chronological and geographic filters applied to four historic subject strengths, providing a sustainable roadmap outlining future acquisitions. The conclusion is that for libraries with restrictive budgets and/or a lack of shelf space, a cost-effective collection assessment process and the development of a focused collections policy posited upon subject depth, rather than breadth, is instrumental in both cost and resource savings.